Exploring Local Wisdom-Based Marketing To Enhance Consumer Attraction At Bu Asih Restaurant In Bandar Lampung City - Aditia Irlanga; Irsandi; Agus Purnomo; Trenggono Pujo Sakti (International Journal of Education, Vocational and Social Science, 2026)
Bu Asih Eatery is a local restaurant located at Jl. Bumi Manti 3 No. 3, Labuhan Ratu, Rajabasa, Bandar Lampung. Although the number of visitors increased from 12,450 in 2022 to 16,950 in 2024, the restaurant's revenue showed a declining trend, decreasing by 5% in 2023 and by 3% in 2024. This decline is partly influenced by reduced menu prices, increased operational costs, the provision of discounts, and rising raw material prices that have suppressed profit margins. This study aims to explore the role of local wisdom-based marketing in enhancing consumer attractiveness at Bu Asih Eatery in Bandar Lampung. This research adopts a qualitative approach, with data collected through interviews, observations, and documentation, and analyzed using qualitative analysis techniques. The results indicate that the implementation of local wisdom-based marketing strategies, through traditional menus, authentic flavors, and friendly service, has successfully built a unique identity and attracted consumers. Factors such as traditional recipes, the use of local ingredients, affordable prices, and a warm atmosphere enhance emotional closeness with customers. Consumers responded positively to the uniqueness of the menu and services. However, challenges include limited resources, conventional promotional methods, and competition from modern restaurants. With proper management, this strategy has the potential to increase customer satisfaction, loyalty, and attract new consumers.